From everyday questions to specialized queries, IDNLearn.com has the answers. Our community is here to provide detailed and trustworthy answers to any questions you may have.
Sagot :
Let's solve the given inequality step by step.
Step 1: Express on a common denominator
We start with the given inequality:
[tex]\[ \frac{x+3}{x-4} > \frac{x-1}{x+6} \][/tex]
To combine the fractions, we find a common denominator, which is [tex]\((x-4)(x+6)\)[/tex].
Rewriting each fraction:
[tex]\[ \frac{(x+3)(x+6)}{(x-4)(x+6)} > \frac{(x-1)(x-4)}{(x-4)(x+6)} \][/tex]
Since the denominators are the same, we can compare the numerators:
[tex]\[ \frac{(x+3)(x+6)}{(x-4)(x+6)} - \frac{(x-1)(x-4)}{(x-4)(x+6)} > 0 \][/tex]
[tex]\[ \frac{(x+3)(x+6) - (x-1)(x-4)}{(x-4)(x+6)} > 0 \][/tex]
Step 2: Simplify the numerator
We need to simplify the expression in the numerator:
[tex]\[ (x+3)(x+6) - (x-1)(x-4) \][/tex]
Expand both terms:
[tex]\[ (x^2 + 9x + 18) - (x^2 - 5x + 4) \][/tex]
Combine like terms:
[tex]\[ x^2 + 9x + 18 - x^2 + 5x - 4 \][/tex]
[tex]\[ 14x + 14 \][/tex]
Factor out the common factor:
[tex]\[ 14(x + 1) \][/tex]
So our inequality is now:
[tex]\[ \frac{14(x+1)}{(x-4)(x+6)} > 0 \][/tex]
Step 3: Determine critical points
Next, find the critical points by setting the numerator and denominator to zero:
[tex]\[ 14(x + 1) = 0 \quad \Rightarrow \quad x = -1 \][/tex]
[tex]\[ x - 4 = 0 \quad \Rightarrow \quad x = 4 \][/tex]
[tex]\[ x + 6 = 0 \quad \Rightarrow \quad x = -6 \][/tex]
The critical points are [tex]\( x = -1 \)[/tex], [tex]\( x = 4 \)[/tex], and [tex]\( x = -6 \)[/tex].
Step 4: Test intervals around the critical points
We divide the number line into intervals using these critical points and test each interval to determine where the inequality holds:
Intervals: [tex]\( (-\infty, -6) \)[/tex], [tex]\( (-6, -1) \)[/tex], [tex]\( (-1, 4) \)[/tex], [tex]\( (4, \infty) \)[/tex]
Choose test points in each interval:
1. [tex]\( x = -7 \)[/tex]:
[tex]\[ \frac{14(-7+1)}{(-7-4)(-7+6)} = \frac{14(-6)}{(-11)(-1)} = \frac{-84}{11} < 0 \][/tex]
2. [tex]\( x = -2 \)[/tex]:
[tex]\[ \frac{14(-2+1)}{(-2-4)(-2+6)} = \frac{14(-1)}{(-6)(4)} = \frac{-14}{-24} > 0 \][/tex]
3. [tex]\( x = 0 \)[/tex]:
[tex]\[ \frac{14(0+1)}{(0-4)(0+6)} = \frac{14(1)}{(-4)(6)} = \frac{14}{-24} < 0 \][/tex]
4. [tex]\( x = 5 \)[/tex]:
[tex]\[ \frac{14(5+1)}{(5-4)(5+6)} = \frac{14(6)}{(1)(11)} = \frac{84}{11} > 0 \][/tex]
Step 5: Assemble solution intervals
The inequality [tex]\(\frac{14(x+1)}{(x-4)(x+6)} > 0\)[/tex] is satisfied in the intervals [tex]\( (-6, -1) \)[/tex] and [tex]\( (4, \infty) \)[/tex].
Step 6: State in interval notation
Since the points [tex]\( x = -6 \)[/tex] and [tex]\( x = 4 \)[/tex] make the denominator zero, and [tex]\( x = -1 \)[/tex] makes the numerator zero, we exclude these points from our solution:
Thus, the solution in interval notation is:
[tex]\[ (-6, -1) \cup (4, \infty) \][/tex]
Step 1: Express on a common denominator
We start with the given inequality:
[tex]\[ \frac{x+3}{x-4} > \frac{x-1}{x+6} \][/tex]
To combine the fractions, we find a common denominator, which is [tex]\((x-4)(x+6)\)[/tex].
Rewriting each fraction:
[tex]\[ \frac{(x+3)(x+6)}{(x-4)(x+6)} > \frac{(x-1)(x-4)}{(x-4)(x+6)} \][/tex]
Since the denominators are the same, we can compare the numerators:
[tex]\[ \frac{(x+3)(x+6)}{(x-4)(x+6)} - \frac{(x-1)(x-4)}{(x-4)(x+6)} > 0 \][/tex]
[tex]\[ \frac{(x+3)(x+6) - (x-1)(x-4)}{(x-4)(x+6)} > 0 \][/tex]
Step 2: Simplify the numerator
We need to simplify the expression in the numerator:
[tex]\[ (x+3)(x+6) - (x-1)(x-4) \][/tex]
Expand both terms:
[tex]\[ (x^2 + 9x + 18) - (x^2 - 5x + 4) \][/tex]
Combine like terms:
[tex]\[ x^2 + 9x + 18 - x^2 + 5x - 4 \][/tex]
[tex]\[ 14x + 14 \][/tex]
Factor out the common factor:
[tex]\[ 14(x + 1) \][/tex]
So our inequality is now:
[tex]\[ \frac{14(x+1)}{(x-4)(x+6)} > 0 \][/tex]
Step 3: Determine critical points
Next, find the critical points by setting the numerator and denominator to zero:
[tex]\[ 14(x + 1) = 0 \quad \Rightarrow \quad x = -1 \][/tex]
[tex]\[ x - 4 = 0 \quad \Rightarrow \quad x = 4 \][/tex]
[tex]\[ x + 6 = 0 \quad \Rightarrow \quad x = -6 \][/tex]
The critical points are [tex]\( x = -1 \)[/tex], [tex]\( x = 4 \)[/tex], and [tex]\( x = -6 \)[/tex].
Step 4: Test intervals around the critical points
We divide the number line into intervals using these critical points and test each interval to determine where the inequality holds:
Intervals: [tex]\( (-\infty, -6) \)[/tex], [tex]\( (-6, -1) \)[/tex], [tex]\( (-1, 4) \)[/tex], [tex]\( (4, \infty) \)[/tex]
Choose test points in each interval:
1. [tex]\( x = -7 \)[/tex]:
[tex]\[ \frac{14(-7+1)}{(-7-4)(-7+6)} = \frac{14(-6)}{(-11)(-1)} = \frac{-84}{11} < 0 \][/tex]
2. [tex]\( x = -2 \)[/tex]:
[tex]\[ \frac{14(-2+1)}{(-2-4)(-2+6)} = \frac{14(-1)}{(-6)(4)} = \frac{-14}{-24} > 0 \][/tex]
3. [tex]\( x = 0 \)[/tex]:
[tex]\[ \frac{14(0+1)}{(0-4)(0+6)} = \frac{14(1)}{(-4)(6)} = \frac{14}{-24} < 0 \][/tex]
4. [tex]\( x = 5 \)[/tex]:
[tex]\[ \frac{14(5+1)}{(5-4)(5+6)} = \frac{14(6)}{(1)(11)} = \frac{84}{11} > 0 \][/tex]
Step 5: Assemble solution intervals
The inequality [tex]\(\frac{14(x+1)}{(x-4)(x+6)} > 0\)[/tex] is satisfied in the intervals [tex]\( (-6, -1) \)[/tex] and [tex]\( (4, \infty) \)[/tex].
Step 6: State in interval notation
Since the points [tex]\( x = -6 \)[/tex] and [tex]\( x = 4 \)[/tex] make the denominator zero, and [tex]\( x = -1 \)[/tex] makes the numerator zero, we exclude these points from our solution:
Thus, the solution in interval notation is:
[tex]\[ (-6, -1) \cup (4, \infty) \][/tex]
We value your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. For dependable answers, trust IDNLearn.com. Thank you for visiting, and we look forward to assisting you again.